Academic word list coverage in published articles written by Uzbek EFL undergraduates: a corpus-based study - Rustamova, Sevinch Akmal qizi; Gulomova, Raykhona Rustamjonovna (The Lingua Spectrum, 2026)
This article investigates the use of academic vocabulary in research papers written in English by Uzbek EFL students through a corpus-based approach. The main objective of the study is to determine the level of Academic Word List (Coxhead, 2000) coverage in student research writing and to identify lexical variation across individual papers. For this purpose, a small corpus consisting of ten research articles produced by Uzbek undergraduate students was compiled and analyzed. The texts were processed using Compleat VocabProfiler, an online lexical profiling tool based on Nation’s frequency lists. Particular attention was given to the Academic Word List, which contains 570 word families commonly found in academic discourse. The findings indicate that the mean AWL coverage across the corpus was 9.07% of total running words. The highest recorded value reached 14.67%, while the lowest result was only 2.01%, demonstrating considerable variation in academic vocabulary use among the analyzed papers. Such variation suggests differences in lexical competence, familiarity with academic writing conventions, and topic-related vocabulary demands. The study highlights the importance of explicit academic vocabulary instruction, corpus-informed teaching methods, and systematic support for academic writing development in Uzbek higher education contexts.